Path Analysis of Health Literacy, Social Support, and Self-Efficacy on Decisional Conflict in Patients with Stable Schizophrenia - He X; Xie Z; Xia Z; Liu X; Wei Y; Yang Y (Neuropsychiatric Disease and Treatment)
Xucong He,1 Zhibin Xie,2 Zhichun Xia,1 Xiulan Liu,3 Yanheng Wei,4 Yong Yang1 1Department of Adult Psychiatry, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, Guangdong Province, People’s Republic of China; 2Department of Clinical One, Third People’s Hospital, Meizhou City, Guangdong Province, People’s Republic of China; 3Department of Chronic Psychiatry, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, Guangdong Province, People’s Republic of China; 4Department of Nursing, The Affiliated Brain Hospital, Guangzhou Medical University, Guangzhou, Guangdong Province, People’s Republic of ChinaCorrespondence: Yong Yang, Department of Adult Psychiatry, The Affiliated Brain Hospital, Guangzhou Medical University, No. 36, Mingxin Road, Liwan District, Guangzhou, Guangdong Province, 510370, People’s Republic of China, Tel +86 020 3152 6759, Email 27747512@qq.comPurpose: Constructing a multiple mediation model based on two mediating variables, social support and self-efficacy, to explore the mechanism of health literacy’s effect on decisional conflict in patients with stable schizophrenia.Patients and Methods: A total of 205 patients with stable schizophrenia who were hospitalized in a psychiatric hospital in Guangdong Province, China, were selected for the study. The All Aspects of Health Literacy Scale (AAHLS), Decisional Conflict Scale (DCS), Social Support Rating Scale (SSRS) and General Self-Efficacy Scale (GSES) were used to evaluate health literacy, decisional conflict, social support and self-efficacy. Path analysis was performed by constructing a structural equation model, and the mediating effect between variables was validated by the bias-corrected nonparametric percentile bootstrap method.Results: Health literacy, social support, and self-efficacy together explained 20.4% of the variance in decisional conflict. (1) Severe decisional conflict group accounted for 82% of overall patients with stable schizophrenia. (2) there were strong and significant negative relationships between decisional conflict and health literacy, social support, self-efficacy and each of their dimensions (r=− 0.14– 0.27, P< 0.01 or P< 0.05). (3) The path analysis showed that health literacy directly affects decisional conflict (β=− 0.282); additionally, health literacy indirectly affects decisional conflict through social support (β=− 0.319), self-efficacy (β=− 0.010) and through the chain mediating effect of social support and self-efficacy (β=− 0.008).Conclusion: Patients with stable schizophrenia have serious decisional conflict in China, and necessary interventions have to be made. This study found that social support and self-efficacy mediate the relationship between health literacy and decisional conflict in patients with stable schizophrenia in China. Healthcare professionals should emphasize health literacy education for patients, and implement pathway-based targeted interventions to improve health literacy, reduce decisional conflict, and promote the recovery of patients with stable schizophrenia.Keywords: stable schizophrenia, decisional conflict, health literacy, mediating role, structural equation model